Informal care and gifts to and from older people in Europe: The interlinks between giving and receiving - Florian Tomini; Wim Groot; Sonila M. Tomini (BMC, 2016)
Abstract Background Transfers of money and help with daily activities by family and friends are important sources of support for older people and contribute to their well being. On the other hand, older adults are not only recipients of support but also important providers of support and financial transfers as giving and receiving are often reciprocal. For this, it is important to understand the determinants of receiving and giving money and help as well as the relationship between these two. Methods The aim of this paper is to explore the relationship between giving and receiving of the same or of different types of transfers as well as to get more insights in the motivation behind giving and receiving of money gifts or informal care. We use data from the Survey of Health Aging and Retirement in Europe and employ a multinomial logit model to analyse 16 different categories resulting from combining information on the incidence of giving and receiving of both informal care and financial gifts. Results We show that despite the differences that exist in the incidence of giving and receiving of both informal care and financial gifts there are clearly a few patterns that are consistent between the European countries in our analysis. Both 'altruistic-like' and 'exchange-like' motives are more likely to increase by age, gender and physical proximity of network members, while 'reciprocal-like' giving and receiving is more likely among females and those with a network at close distance. Conclusions Our results show that the incidence of informal care and gifts to and from older people is related to particular characteristics and transfers patterns. Further research should be dedicated to exploring the situations leading to the 'altruistic-like' and 'exchange-like' combinations of transfers.